Absolute Competence and Characteristics of the Object of State Administrative Disputes in Electricity Infrastructure Construction - Prakoso, Angga Dwian; Khusnawati, Atik Amalia; Kusumastuti, Purnaning Siwi; Aulia, Ayi Rayhana; Iswahyudi, Agus (SIGn Journal of Social Science, 2025)
National electricity infrastructure development often triggers complex construction disputes due to the overlap between civil law and state administrative law. This research aims to analyze the parameters of the State Administrative Court’s absolute competence, identify the juridical characteristics of dispute objects, and formulate a legal protection framework for construction service providers. The research method utilized is normative legal research, with a statute-based and conceptual approach. Data were analyzed qualitatively through deductive reasoning on twenty authoritative secondary literature sources. The research results show that the absolute competence of the administrative judiciary is rigidly determined by the source of public authority (acta jure imperii) used by the government in its capacity as manager of the strategic energy sector. The characteristics of dispute objects in the electricity ecosystem have undergone significant expansion following the enactment of Law Number 30 of 2014. These objects now encompass factual actions such as change order instructions, location determination, and blacklist administrative sanctions. The analysis shows that state administrative officials’ decisions in the substation and power transmission licensing process constitute valid grounds for judicial review to prevent abuse of discretion. The research conclusion affirms that the legal reasoning pattern must emphasize legality review based on the General Principles of Good Administration. Optimizing the decision suspension instrument is also required as an emergency measure to protect business actors. More harmonious alignment between construction service law and administrative law is required to ensure legal certainty and the sustainability of national electricity infrastructure development.